DETERMINAN KEPUASAAN KERJA PADA KINERJA KARYAWAN DENGAN PENDEKATAN TEORI DUA FAKTOR - Stefanus Rumangkit; Ary Wijayati Kusumaningtyas (Jurnal Bisnis Darmajaya, 2023)
The purpose of this research is to investigate job security, compensation, and interpersonal relationships on job satisfaction. In addition, the purpose of this study was to see the impact of job satisfaction on job performance. This study uses a quantitative approach, and uses primary data. Questionnaires are used as a data collection tool. Respondents in this study were 100 respondents. The sampling technique used purposive sampling, with the condition that they are employees in private companies who have worked for 1 year or more. Data analysis tool using SmartPLS. The results of this study are job security has an effect on job satisfaction, compensation has an effect on job satisfaction, interpersonal relationships have an effect on job satisfaction, and the final finding of this research is job satisfaction has an effect on job performance.Keywords : Job Satisfaction, Job Performance, Job Security, Compensation, Interpersonal Relationship